Nonsurgical Treatment of Male Infertility: Non-Specific Therapy - Metin Öztürk; Emre Tokuç (Düzce Tıp Fakültesi Dergisi, 2022)
In male infertility, all possible known causes should be carefully evaluated and if detected, targeted treatment options for the cause should be implemented. The known causes of male infertility such as hypogonadotropic hypogonadism, hyperprolactinemia, genital tract infections, disorders of ejaculation, thyroid hormone disorders and varicocele can be treated efficiently by targeted therapies or surgical corrections. Unfortunately, these known causes cover about 20% of male infertility and the rest remains idiopathic. On the other hand, management of idiopathic, unexplained male infertility, in which no etiological factors can be found, is a challenge for both the clinician and couples seeking solutions. In the era of assisted reproductive technology, few medical options in this regard are still available with limited benefits and low scientific foundation based on theoretical concepts but empirical medical therapy continues as a mostly off-label option for obtaining a natural pregnancy. Comprehending the hypothalamic-pituitary-gonadal axis and the regulation of hormones is crucial in this regard. Empirical therapies have the potential to overcome overtreatment with assisted reproductive technology yet clinicians and couples must be aware of the limitations of empirical therapies and should be counseled in this direction. In this review, non-specific medical treatment options for idiopathic male infertility were covered.